Aksi Plogging Kesadaran Kebersihan Lingkungan Di Balige Oleh P3mi Jemaat Manna Balige - Lestari Br. Silaban; Yubilate Chriswell Zebua; Fa'atulo Gulo (Jurnal Pengabdian Dian Mandala, 2024)
Plogging is an activity that combines jogging with trash collection. In Balige, this activity was carried out by the Balige Methodist Church Youth Fellowship (P3MI) to increase environmental awareness among youth and the surrounding community. This research aims to evaluate the effectiveness of plogging activities in increasing awareness and maintaining environmental cleanliness. The results show that this activity was successful in collecting around 12 sacks of 50 kg rubbish, increasing participants' awareness about environmental cleanliness, and getting a positive response from the public who saw this action. Recommendations for the sustainability of this activity include regular implementation, involvement of more communities, and educational campaigns about reducing plastic.